2022
DOI: 10.1177/10556656221112672
|View full text |Cite
|
Sign up to set email alerts
|

Is the Message Clear? Evaluation of Readability Levels for Cleft Lip, Cleft Palate, and Craniofacial Websites

Abstract: Web-based health information is the leading source of medical knowledge for patients and families. The American Medical Association (AMA) and US Department of Health and Human Services recommend reading material be at or below a sixth-grade reading level. This study aimed to evaluate and compare the readability of the most popularly searched cleft lip and/or palate (CL/P) and other craniofacial syndrome (CFS) websites. Google searches for “cleft lip,” “cleft palate,” and “craniofacial syndromes” were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Evaluation of readability using both FRES, which determines the ease of reading based on the average length of words and sentences, and FKGL, which determines the United States grade level of text based on average sentence length and syllables per word, indicates that less than 40% of all websites reviewed had a standard reading level, and only 5.3% were written at the recommended level of 6th grade. 5 These results align with previous studies on pediatric and adult facial plastic surgery procedures that found inconsistencies between patient information and the recommended 6th grade reading level 21,22,24,25,2933 . In 2022, a scoping review of 36 previously published studies examined the readability of online patient information for plastic surgery procedures, which represents the largest analysis of educational material for the plastic surgery patient to date (n = 1539).…”
Section: Discussionsupporting
confidence: 84%
“…Evaluation of readability using both FRES, which determines the ease of reading based on the average length of words and sentences, and FKGL, which determines the United States grade level of text based on average sentence length and syllables per word, indicates that less than 40% of all websites reviewed had a standard reading level, and only 5.3% were written at the recommended level of 6th grade. 5 These results align with previous studies on pediatric and adult facial plastic surgery procedures that found inconsistencies between patient information and the recommended 6th grade reading level 21,22,24,25,2933 . In 2022, a scoping review of 36 previously published studies examined the readability of online patient information for plastic surgery procedures, which represents the largest analysis of educational material for the plastic surgery patient to date (n = 1539).…”
Section: Discussionsupporting
confidence: 84%